PENGARUH PUBLIC SPEAKING, PENGUASAAN TEKNOLOGI INFORMASI, DAN MANAJEMEN WAKTU TERHADAP KESIAPAN KERJA MELALUI SELF-EFFICACY MAHASISWA (STUDI KASUS MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN STAMBUK 2023 UNIVERSITAS NEGERI MEDAN) - Nazla Ritonga; Hasyim Hasyim (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Work readiness is one of the essential competencies that university students need to possess in order to face increasingly dynamic and competitive labor market demands. This study aimed to analyze the effects of public speaking, information technology mastery, and time management on work readiness through self-efficacy as an intervening variable among students of the Office Administration Education Study Program, Class of 2023, Faculty of Economics, Universitas Negeri Medan. This study employed a quantitative approach with a causal associative design. The population consisted of all students of the Office Administration Education Study Program, Class of 2023, and the sampling technique used was saturated sampling, resulting in 71 respondents. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results revealed that information technology mastery and self-efficacy had a positive and significant effect on work readiness, whereas public speaking and time management did not have a significant direct effect on work readiness. Furthermore, public speaking and time management had a positive and significant effect on self-efficacy, while information technology mastery did not significantly affect self-efficacy. The findings also indicated that self-efficacy mediated the relationship between public speaking and work readiness as well as between time management and work readiness, but it did not mediate the relationship between information technology mastery and work readiness. Therefore, strengthening students' self-efficacy is necessary to enhance their work readiness.